A cross‐sectional study of vitreous and serum high mobility group box‐1 levels in proliferative diabetic retinopathy. Issue 2 (17th August 2019) - Shen, Yinchen; Cao, Hui; Chen, Feng'e; Suo, Yan; Wang, Ning; Xu, Xun
Abstract: Purpose: We determined vitreous and serum levels of high mobility group box‐1 (HMGB‐1) in patients with proliferative diabetic retinopathy (PDR) and elucidate their relationship with receptor for advanced glycation end products (RAGE), vascular endothelial growth factor (VEGF) and interleukin‐1 β (IL‐1 β ). Methods: In this cross‐sectional study, patients with PDR who underwent vitrectomy were enrolled, and the control group included non‐diabetic eyes. Vitreous and serum samples were analysed for HMGB‐1, RAGE, VEGF and IL‐1 β by ELISA. We investigated the correlation between serum and vitreous levels of each cytokine, and we analysed the influence of intravitreal anti‐VEGF treatment prior to vitrectomy on the cytokine levels in PDR. Results: Of 78 eyes of 78 patients enrolled consecutively, there were 32 PDR eyes and 46 control eyes. The serum levels were higher in diabetic than in non‐diabetic subjects for HMGB‐1, RAGE, VEGF and IL‐1 β (all p < 0.001), respectively. Similarly, the vitreous levels were higher in diabetic than in non‐diabetic subjects for HMGB‐1 (p < 0.001), RAGE (p = 0.001), VEGF (p < 0.001) and IL‐1 β (p < 0.001), respectively. We found a positive correlation between serum and vitreous levels of HMGB‐1 in patient with PDR (p = 0.047, R = 0.353). There was a negative correlation between serum and vitreous levels of VEGF in patient with PDR (p = 0.001, R = −0.546). For the subgroup analysis, we detected that the vitreous levels of RAGE were significantly lower in patients who underwent anti‐VEGF injection prior to vitrectomy than those who did not (p < 0.001). Conclusions: Our findings suggest that HMGB‐1 is involved in PDR disorders, and it may be a novel therapeutic target to inhibit progression of PDR.